Effects of Public Expenditure on Gross Domestic Product in Zambia from 1980-2017: An ARDL Methodology Approach - Mubanga Mpundu; Jane Mwafulirwa; Mutinta Chaampita; Notulu Salwindi (Journal of Economics and Behavioral Studies, 2019)
The paper explored the fundamental changes in public expenditure and the resulting effect on the gross domestic product using an ARDL approach for time series data over the period 1980-2017. The control variables included foreign direct investment and current account balance. The objective was to determine changes which had occurred with regard to the performance of GDP since 1980. A quantitative method approach was used to ascertain the relationship between the variables and analysed using the E-views 9 software. Cointegration results showed a long run relationship between GDP and government expenditure. In this regard, changes in government expenditure have a strong converse effect on GDP. Government expenditure, which has increased significantly in the past decade, is seen to have had negative effects both in the short run and long run. Contrary to theory, increased government expenditure may not be ideal for growing the Zambian economy. This could be due to the allocation of this public expenditure, i.e. the 2018 Budget had 24% of the expenditure directed to economic activities. Thus it is recommended that government practice increased fiscal discipline or reallocated resources as their expansionary fiscal policies are not yielding the intended results. Additionally, policies to promote private investment may be more beneficial for the Zambian economy. On the other hand, increased investment is also recommended with government encouraging more investment promoting policies as FDI is observed to have a positive impact in the short run though insignificant in the long run. These should ensure more investors are encouraged to stay longer and the impacts/externalities of their investments be accrued to the nationals to ensure long run benefits. The Zambian government should also ensure that the country diversifies its export base and enhances its external debt management to ensure positive and consistent impact of Current Account Balance in the long run.